Willingness to Accept dan Willingness to Pay Petani dan Konsumen terhadap Padi Hibrida di Sentra Produksi Jawa Timur - Adnyana, Made Oka; Wardana, Putu (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
Research on hybrid rice in Indonesia was initiated in 1983, in collaboration with the International Rice Research Institute. Since 2000 private sector had indicated their interest in hybrid rice seed business. Planted area of hybrid rice in Indonesia was still relatively small of about 658 thousand hectares or about 5.0 percent of the total rice planted area of 13.2 million hectares in 2013. This study was aimed to analyze farmersâ€™ responses and preferences to the development of hybrid rice in East Java, one of the rice production center in Indonesia. Contingent valuation method (CVM) to analyze farmersâ€™ Willingness to Accept (WTA) and Willingness to Pay (WTP) with respect to various factors was then exercised to evaluate constraints and prospect of the future of hybrid rice development in Indonesia. The outputs of this study showed that farmersâ€™ preferences to hybrid rice based on its taste was positive, especially to the newly introduced hybrid rice variety â€œHipa Jatimâ€, when compared with the previous hybrid varieties, such as Maro and Rokan. WTA and WTP also showed significant farmersâ€™ interests to the hybrid variety, due to higher yield and its better taste, similar to that of popular inbred rice. Farmersâ€™ WTAs of hybrid rice was significantly influenced by the productivity, response to pests and deseases, and the total cost of production, while consummersâ€™ WTPs of hybrid rice was significantly influened by the quality of milled rice.